Contribuições para a investigação da problemática da Ideologia Punitiva - Igor dos Santos Kroeff (2020)
This research aims to contribute to the fight against the political mistake known as the “punitive left”. Therefore, it was necessary to try to force the advance of the Marxist theory of ideology from the attempt to identify a particular ideology, specifically the Punitive Ideology, seeking to unveil its material roots, its subordinate and overdetermined character, among complex articulations and reciprocal influences practiced in the ideological field. With this objective, it was necessary to resort to the theoretical instruments provided by Louis Althusser, especially in what concerns the contributions contained in his manuscript “On the Reproduction of Capitalism”, but taking into account all of his work, with his self-criticisms, advances and obstacles, as much as possible. Thus, the present theoretical practice has as its starting point the demarcation of the materialist position of the research, through the exposure of the overdetermined character of the spheres of the social whole, highlighting that the exploitation of classes occurs, above all, in production, while state violence of class occurs contingently. In sequence, the most significant contributions of Louis Althusser are used to try to carry out a scientific investigation in the ideological field, followed by his positions about the State and its apparatus, as well as his indications about the centrality of the legal-moral ideology in the capitalist mode of production. At this point, a dialogue was held with close authors, who contribute to the delineation of the problem, with emphasis on Evgeni Pachukanis. Finally, this essay was made for the identification and investigation of Punitive Ideology as a secondary ideology subordinated to moral legal ideology, taking into account the theoretical supports presented, enabling the rejection of humanist positions in the critique of the “punitive left” and, thus, more consistent political action in this field.